Promoting Inclusive Growth by Creating Opportunities for the Urban Poor : Philippines Urbanization Review Policy Notes - World Bank (World Bank, Washington, DC, 2017)
This policy note discusses promoting inclusive growth by creating opportunities for the urban poor and is part of a broader Philippines urbanization study. Inclusive urbanization requires an integrated multi-dimensional approach that addresses three key dimensions of inclusion – economic, spatial, and social. The three dimensions of inclusion are interrelated and mutually reinforcing. Currently cities fail to keep pace with the rapid urbanization in the Philippines and multi-dimensional poverty in urban areas is deepening and widening. With in-migration from rural areas to urban centers came surges in demand for jobs, housing, infrastructure and basic services in major cities. Yet, the Government has been unable to address the increased demand given the accelerated pace. The result has been proliferation of informal settlers in urban areas without adequate access to decent living conditions. Addressing urban poverty and inequality remains an important challenge for the Philippines and will require a holistic approach that integrates all dimensions of inclusive urbanization.